A New Spinal Cord Stimulation Option: High-frequency 10 Kilohertz (HF10®). - Campbell, Kelly; Vargas, Joanna (Journal of Life Care Planning, 2018)
Spinal cord stimulation is a widely-used modality used to treat pain conditions for individuals who have chronic pain that has not responded to traditional interventions including medication, surgery or physical therapy. Life care planners often include spinal cord stimulation in the life care plans that they prepare for individuals with pain. This article will introduce life care planners to a new type of spinal cord stimulation, high-frequency 10 kilohertz HF10® therapy provided by Nevro Corporation. Efficacy data of HF10® is also included. Guidelines for requisite current procedural terminology (CPT) codes are also provided.